RELATIONSHIP BETWEEN NURSING SERVICE QUALITY AND PATIENT SATISFACTION IN EMERGENCY INSTALLATION dr. HASRI AINUN HABIBIE HOSPITAL GORONTALO PROVINCE - Meiti Yolanda; Nasrun Pakaya; Siti Hajar Salawali (PT. Jurnal Center Indonesia Publisher, 2025)
Nursing Service Quality and Patient Satisfaction have a close relationship in determining patient response to service . Patient satisfaction and dissatisfaction responses depend on the service provided by the nurse. This research uses a descriptive design with a quantitative approach . cross-sectional. in the emergency installation of dr. Hasri Ainun Habibie Hospital, the number of respondents was 60 with the sampling technique in this study using Accidental sampling. . Quality of Nursing Services in the Emergency Installation of Dr. Hasri Ainun Habibie Hospital, Gorontalo Province Most of them provide maximum services with the Good category as many as 29 respondents (48.3%). and Patient Satisfaction in the Emergency Installation of Dr. Hasri Ainun Habibie Hospital, Gorontalo Province Most of them were also satisfied with 36 respondents (60.0%), but most of them were still dissatisfied with 24 respondents (40.0%). The results of the Chi-square statistical test obtained a significant value or p-value (0.000) lower than the significant standard of 0.05 or (p <α), then Ho was rejected and H1 was accepted, which means there is a relationship between the quality of nursing services and patient satisfaction in the emergency installation of Dr. Hasri Ainun Habibie Hospital, Gorontalo Province.